Synthesis of poly(methyl methacrylate) core/chitosan-mixed-polyethyleneimine shell nanoparticles and their antibacterial property - Supharat Inphonlek (2018)
The core-shell nanoparticles possessing poly(methyl methacrylate) (PMMA) core coated with chitosan (CS), polyethyleneimine (PEI), and chitosan-mixed-polyethyleneimine (CS/PEI) shells were synthesized in this work. The emulsifier-free emulsion polymerization triggered by a redox initiating system from t-butylhydroperoxide (TBHP) and amine groups on CS and/or PEI was used as a synthetic method. In the CS/PEI systems, the amount of CS was kept constant (0.5. g), while the amount of PEI was varied from 0.1 to 0.5. g. The surface and physico-chemical properties of prepared nanoparticles were then examined. FTIR spectra indicated the presence of grafted PMMA on CS and/or PEI, and the weight fraction of incorporated PEI in the CS/PEI nanoparticles. All nanoparticles were spherical in shape with uniform size distribution illustrated by scanning electron microscopy (SEM). The introduction of PEI to CS nanoparticles yielded the higher monomer conversion, grafting efficiency, and grafting percentage compared with the CS nanoparticles. The size of CS/PEI nanoparticles was smaller than the original CS and PEI nanoparticles, and tended to decrease with increasing amount of PEI introduced. The introduction of PEI also brought the higher colloidal stability to the nanoparticles as indicated by zeta-potential measurement and isoelectric point analysis. The nanoparticles exhibited a promising antibacterial activity against Staphylococcus aureus and Escherichia coli. The nanoparticle-bacteria interaction was studied via SEM. The results suggested that they would be useful as effective antibacterial agents. © 2010 Elsevier B.V.